IDENTIFICATION OF INDOOR HEALTH COMFORT (IHC) AT TANJUNGPURA UNIVERSITY LIBRARY BASED ON GBCI RATING TOOLS - Cinthia Junita Milenia; Lestari Lestari; Valentinus Pebriano (JMARS: Jurnal Mosaik Arsitektur, 2023)
Most human activities are carried out in an indoors space. The room as an activity support facility must be able to provide a sense of comfort and safety and provide the health impacts needed by its occupants. Unhealthy working conditions can cause SBS (Sick Building Syndrome). SBS is a health problem and discomfort during activities in the room, which gradually disappears when the room user leaves the building. SBS causes a decrease in room user’s health, comfort, and productivity. To prevent this, identification of indoor health and comfort or IHC based on Greenship Interior Space is required. The object of this research is the Tanjungpura University Library, which has fulfiled the green construction criteria in terms of previous research. The study used an evaluative method by measuring the assessment referring to the Greenship Interior Space version 1 standard with field observations, simulations, manual calculations, and evaluation interviews. The results of analysis shows that the building achieves a score of 14 out of the maximum score of 28 with a value of 50%. The building successfully fulfilled prerequisite criteria, CO2 levels, chemical pollutants, biological pollutants, visual comfort, views from the outside and sunlight, and user comfort. It is hoped that the research results can be proposed as the right strategy to improve indoor health and comfort conditions at the Tanjungpura University Library building.